Treatment Progress of Immune Checkpoint Blockade Therapy for Glioblastoma - Zhang, Na; Wei, Li; Ye, Meng; Kang, Chunsheng; You, Hua (Frontiers in Immunology, 2020)
Glioblastoma (GBM) is a highly malignant and aggressive primary brain tumor mostly prevalent in adults and is associated with a very poor prognosis. Moreover, only a few effective treatment regimens are available due to their rapid invasion of the brain parenchyma and resistance to conventional therapy. However, the fast development of cancer immunotherapy and the remarkable survival benefit from immunotherapy in several extracranial tumor types have recently paved the way for numerous interventional studies involving GBM patients. The recent success of checkpoint blockade therapy, targeting immunoinhibitory proteins such as programmed cell death protein-1 and/or cytotoxic T lymphocyte-associated antigen-4, has initiated a paradigm shift in clinical and preclinical investigations, and the use of immunotherapy for solid tumors, which would be a potential breakthrough in the field of drug therapy for the GBM treatment. However clinical trial showed limited benefits for GBM patients. The main reason is drug resistance. This review summarizes the clinical research progress of immune checkpoint molecules and inhibitors, introduces the current research status of immune checkpoint inhibitors in the field of GBM, analyzes the molecular resistance mechanism of checkpoint blockade therapy, proposes corresponding re-sensitive strategies, and describes a reference for the design and development of subsequent clinical studies on immunotherapy for GBM.